Women’s awareness and preferences for birthing positions: a comparison with midwifery practices, a study conducted in Chikhwawa district - Nyirongo, Tiwonge Ndindase (2021)
This study aimed at determining women’s awareness of birthing positions as well as their preferences for any particular position. Studies have shown that the supine birthing position during labour and delivery has many disadvantages to the mother, the foetus and on the progress of labour. In health facilities, women mostly use the supine position for delivery. This forces some women to deliver in their homes. This cross-sectional, descriptive quantitative study was conducted at Chikhwawa District Hospital, St Montfort Hospital and Mfera Health Centre in Chikhwawa District. A total of 267 women aged 18 to 50, having at least a second pregnancy or second birth attending antenatal and postnatal services and17 midwives working in the labour wards of the three facilities were recruited in the study. The data for the women was collected using an interview schedule and an observational checklist was used for the midwives. The data was analysed using Statistical Package for the Social Sciences (SPSS) version 20. Ninety eight percent (n=261) of the women were aware of the supine position and the sitting position was known by only 21% (n=56) of the women. Thirty two percent of the women had in-depth knowledge of the benefits of the upright positions and only12% (n=31) of the women preferred to use upright position. The women’s location had an influence on their knowledge of the benefits of upright positions (χ2=24.05; P value=0.001) and the women’s age had an influence on their preference for upright positions (χ2=21.14; p-value=0.002). There were no information, education and communication (IEC) materials and equipment for positioning the women in upright position and all the midwives used the dorsal position when conducting the deliveries. Overall, there was some knowledge gap on upright positions among the women as well as the midwives. Midwives should therefore be empowered with knowledge and skills for the upright positions and the women should be equipped with knowledge of the various positions so that they should make informed choices.